EEG Differences in Two Clinically Similar Rapid Dementias: Voltage-Gated Potassium Channel Complex–Associated Autoimmune Encephalitis and Creutzfeldt-Jakob Disease. (March 2019) - Freund, Brin; Probasco, John C.; Cervenka, Mackenzie C.; Sutter, Raoul; Kaplan, Peter W.
Distinguishing treatable causes for rapidly progressive dementia from those that are incurable is vital. Creutzfeldt-Jakob disease (CJD) and voltage-gated potassium channel complex–associated autoimmune encephalitis (VGKC AE) are 2 such conditions with disparate outcomes and response to treatment. To determine the differences in electroencephalography between CJD and VGKC AE, we performed a retrospective review of medical records and examined clinical data, neuroimaging, and electroencephalographs performed in patients admitted for evaluation for rapidly progressive dementia diagnosed with CJD and VGKC AE at the Johns Hopkins Hospital and Bayview Medical Center between January 1, 2007 and December 31, 2015. More patients in the VGKC AE group had seizures (12/17) than those with CJD (3/14; P = .008). Serum sodium levels were lower in those with VGKC AE ( P = .001). Cerebrospinal fluid (CSF) white blood cell count was higher in VGKC AE ( P = .008). CSF protein 14-3-3 ( P = .018) was more commonly detected in CJD, and tau levels were higher in those with CJD ( P < .006). On neuroimaging, diffusion restriction in the cortex ( P = .001), caudate ( P < .001), and putamen ( P = .001) was more frequent in CJD. Periodic sharp wave complexes ( P = .001) and generalized suppressed activity ( P = .008) were more common on initial EEG in CJD. On serial EEGs, generalized periodic discharges ( P = .004), generalized suppressed activity (P=0.008), and periodic sharp wave complexes ( P < .001) were detected more in CJD. This study shows that there are a number of differentiating features between CJD and VGKC AE, and electroencephalography can aid in their diagnoses. Performing serial EEGs better delineates these conditions.